Gas flows and feedback in star-forming galaxies - Tafere, Melaku S. (Department of Astronomy, 2019)
In this MSc thesis, I investigated the kinematics of Hα emission from the hot ionized and NaD absorption from cool neutral gas in a sample of 40 nearby Luminous Infrared Galaxies (LIRGs: LIR ≥1011L) from Supernovae and starbursts in the infrared, SUNBIRD survey imaged with the Southern African Large Telescope (SALT). This project can be seen in two major areas. The first is analyzing the emission and absorption spectra, in this case from the hot ionized gas and cool gas respectively. Two routines were used for the profile fitting, to get the centroid wavelength of both the emission and absorption lines; Gaussian and Gaussian-Hermite functions were used. The fitting result provides an indication of the origin of an outflowing gas; nuclear or disk driven?. Secondly, I plotted and compared the velocities of hot ionized and cool neutral gas. Three different methods were used to estimate the systemic velocity Vsys for the accurate estimation of outflowing velocity. For instance, an outflowing NaD upto 380 kms−1 and inflowing gas up to -100 kms−1 relative to Hα is seen at the optical nucleus of the NGC6240[PA=45] and NGC1204[PA=253] galaxies respectively. I tested if there was a relation between star formation rate (SFR) and an outflowing gas and also whether the inflowing gas triggering new nuclear SF. I find the gas of two of our targets escaping the potential well of the host galaxy. There was also an expectation that the out flowing velocity would correlate with SFR, unfortunately I do not see any correlation, though it needs further investigation of all offset velocities of the gas with respect to stellar absorption lines and it also requires detail analysis of the of projection or orientation effect on the galaxy.